Mushaf İmlasında Ali el-Kârî Tarzı Meselesi - (:unkn) unknown (My University, 2015)
Hz. Osman'ın istinsah ettirdiği mushafların kendine mahsus bir imlası vardır. "Resm-i Osmânî" denilen bu imla, bazı noktalarda "kıyasî imla"dan farklılık göste-- rir. Mushaf yazımında ekseriyetle bu imlaya riayet edilmiştir. Ancak bazen bu imlanm dışına çıkıldığı da olmuştur. Nitekim Türkiye'de basılan mushaflar böyledir. Türkiye mushaflarındaki imlanın Ali el--Kârî'ye dayandığı iddia edilir ve "Ali el--Kârî tarzı" olarak adlandırılır. Bu çalışmada, söz konusu iddianın muhtemel dayanakları araştırılarak Ali el-Kari'nin mushaf imlası konusunda bir tarz geliştirip geliştirmediği sorgulanmaktadır. İddianın muhtemel dayanaklarından alınan imla örnekleri mukayese edilerek Ali el--Kârî'nin mushaf imlası konusunda bir tarz ortaya koymadığı, ona nispet edilen bu tarzın çok önceki dönemlerde var olduğu sonucuna ula-- şılmaktadır.

The texts of the Qur’an duplicated by the third caliph Uthman has special orthography. This special style of writing called “aZ—Rasm al—Uthmani” presents differences at certain points from the regular rules of orthography. In the orthography of the texts of the Qur’an, the regular rules have usually been followed, but oc— casionally some of the rules have not been followed. The texts of the Qur’an published in Turkey can be listed among the latter type. The orthography followed in the texts of the Qur’an published in Turkey is claimed to go back to Ali al-Qari and thus it is called the style of Ali al-Qari. In this article, the bases of this claim are examined and it is questioned whether Ali al—Qari developed style regarding the orthography of the texts of the Qur’an. As result of comparison among the sam— ples taken from the possible bases of this claim, it is concluded that Ali al-Qari did not develop style regarding the orthography of the texts of the Qur’an, and the style attributed to his name had existed much earlier than his lifetime.
The Style of Ali al-Qiri on the Ortography of the Quran
Keywords: Din Bilimi